Efektivitas Pemberian Lidah Buaya terhadap Pertumbuhan Jaringan Luka Diabetes Melitus di Panti Sosial Bina Daksa Budi Bakhti 2 - Sutan Fachru Rozy; Ns. Karyatin, M.Kep. (Jurnal Kesehatan STIKes Sumber Waras, 2025)
Background: Diabetic foot ulcers are a complication of diabetes mellitus (DM) that occur due to pressure on the lower extremities and are often associated with other complications. Aloe vera has been shown to promote tissue growth in wounds, thereby aiding the healing process. Objective: To identify the effectiveness of aloe vera in promoting tissue growth in diabetic mellitus wounds. Methods: This study employed a case study method by providing wound care interventions for seven consecutive days, once daily for 30 minutes, to elderly clients with diabetic ulcers on the lower extremities at PSBDBB 2 Cengkareng. Results: The findings demonstrated positive outcomes in wound care using the non-pharmacological technique of aloe vera extract application, as evidenced by changes in wound color and tissue growth. In respondent 1, the wound color changed from pale red with less than 50% granulation tissue to pink with more than 50% granulation tissue. In respondent 2, the wound color changed from pale red to pink. Conclusion: Wound care using aloe vera extract can support the healing process in patients with type II diabetic ulcers. Keywords : Aloe Vera, Tissue growth, Diabetic wounds.